Psychometric properties of the Iranian version of the Copenhagen Burnout Inventory - Elham Javanshir; Iman Dianat; Mohammad Asghari-Jafarabadi (Tabriz University of Medical Sciences, 2019)
Background: The Copenhagen Burnout Inventory (CBI) is a commonly used tool for evaluation of job burnout in three (personal, work-related and client-related) domains. The aims of this study were to translate and investigate the psychometric properties of the Iranian (Persian) CBI. Methods: A total of 750 employees of different occupations (from educational centres, healthcare, industrial settings, and social services) participated in this descriptive methodological study. Aforward-backward procedure was applied and content validity was evaluated by a panel of10 experts. Exploratory and confirmatory factor analyses were used for construct validity. The internal consistency (using Cronbach's alpha), test-retest reliability (using intraclass correlation coefficient - ICC), and feasibility (using ceiling and floor effect) were also assessed for this tool. Results: Content validity of the Persian CBI was established. Three-factor structure of the PersianCBI was supported by the factor analysis, and this confirmed the construct validity of the instrument. The internal consistency (Cronbach's alpha ranged from 0.82 to 0.90) and test-retest reliability (ICC ranged from 0.85 to 0.95) were excellent and there was no ceiling or floor effect. Conclusion: The Persian CBI is a valid and reliable measurement tool for burnout in the Iranian context.